2020
DOI: 10.1111/jvim.15936
|View full text |Cite
|
Sign up to set email alerts
|

Ecological level analysis of primary lung tumors in dogs and cats and environmental radon activity

Abstract: Background: Epidemiologic studies suggest residential radon exposure might increase the risk of primary lung cancer in people, but these studies are limited by subject mobility. This limitation might be overcome by evaluating the association in pets. Hypothesis: Primary pulmonary neoplasia (PPN) rate is higher in dogs and cats residing in counties with a high radon exposure risk (Environmental Protection Agency [EPA] zone 1) compared to zones 2 (moderate radon exposure risk) and 3 (low radon exposure risk). An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
2
0
3
Order By: Relevance
“…Our analysis focused on data with high level of aggregation, and no clear effect of geography variation at district level on malignancy appeared, after the data structure analyzed. The analysis also does not capture effects from narrower closer environmental factors, such as indoor pollution caused by various carcinogens such as tobacco, radon, and others, which may have a stronger influence on malignancy [ 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis focused on data with high level of aggregation, and no clear effect of geography variation at district level on malignancy appeared, after the data structure analyzed. The analysis also does not capture effects from narrower closer environmental factors, such as indoor pollution caused by various carcinogens such as tobacco, radon, and others, which may have a stronger influence on malignancy [ 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de o câncer ser mundialmente a principal causa de morte em homens e mulheres, as taxas de incidência e mortalidade variam em todo o mundo. Diversas variáveis socioeconômicas são capazes de influenciar na incidência do câncer de pulmão, tais como o acesso e qualidade do sistema de saúde, acesso aos métodos de diagnóstico precoce e tratamento direcionado, acesso a informação e conscientização acerca dos fatores de risco, hábitos culturais, exposição ocupacional, alimentação, fatores genéticos, entre outros (BARTA et al, 2019;FOWLER et al, 2020;INCA, 2021).…”
Section: Discussionunclassified
“…A formação de uma neoplasia se inicia a partir da alteração genética herdada ou adquirida, sendo a última gerada espontaneamente ou induzida por processos endógenos ou exógenos. Isto pode ocorrer através da exposição a radiações ionizantes, vírus oncogênicos e substâncias químicas como arsênico, asbesto, berílio, cromo, radônio, urânio, níquel, cádmio, cloreto de vinila e éter de clorometil (UEHARA et al, 1998;KUSEWITT e RUSH, 2009;KUMAR et al, 2013;BADE et al, 2020;FOWLER et al,2020). Ainda, estudos revelam a existência de células iniciadoras tumorais que participam na carcinogênese e conferem ao tumor resistência à quimioterapia (SULLIVAN et al, 2010;ZAKARIA et al, 2018).…”
Section: Neoplasias Pulmonaresunclassified
See 1 more Smart Citation
“…Risk factors of pulmonary carcinoma include exposure to secondhand smoke and as in other cat cancers increased age but with no higher prevalence among breeds or sex 94 . A recent study has concluded that in areas with high radon exposure, companion animals have a 2-fold higher incidence of primary pulmonary neoplasia 95 . Signs of this cancer include coughing, weight loss, lethargy, lameness, and respiratory changes 31,94 .…”
Section: Pulmonary Carcinomamentioning
confidence: 99%